Characterization of vegetable fibers and their application in cementitious composites - Correia, V. C.; Santos, S. F. [UNESP]; Tonoli, G. H.D.; Savastano, Holmer (Elsevier, 2019)
This chapter presents vegetable fibers and their potential for the reinforcement of cementitious materials. Different approaches for improving the processing, physical-mechanical performance and durability of nonconventional fiber-cement composites are highlighted in order to demonstrate the capability of the vegetable fibers for engineering applications. Beyond the introduction to vegetable fibers, the content of this review is divided in the following topics: (i) characterization of the fibers from nano-to macro scales; (ii) a case study of bamboo fibers production; (iii) their application as optimized reinforcement of cement based composites; and (iv) an overview of the composite behavior after exposure to accelerated aging conditions. Final remarks briefly discuss future research needs.
Keywords: Durability; Engineered composites; Fiber characterization; Fiber-cement; Macrofibers; Nanofibers; Natural fibers; Pulp fibers; Pulping process; Reinforcing elements